NETWORK DESIGN OPTIMIZATION AND SEA TOLL SERVICE ROUTES ON THE MARITIME TRANSPORTATION NETWORK - Max Damara Gugat, Rudy
This paper presents the design of the sea toll network, especially in choosing the combination of sea toll networks that have the best performance, in terms of profit and benefit. The problem at hand is the selection of the best combination in the model which is a combinatorial optimization problem. To overcome this problem, a mathematical model was developed using a bi-level programming problem approach. The lower-level problem is related to network loading due to the operation of sea tolls, while the top-level problem is related to the selection of the optimal combination of sea toll networks. The best combination selection optimization technique is done using dynamic programming optimization based on complete enumeration and pareto optimization methods. This process involves calculating and analyzing various combinations of sea toll operating systems in achieving optimal solutions, in the form of optimal performance of profits and benefits, where the profit calculation process involves calculating the difference between revenue and transportation operational costs with and without sea toll operations. Meanwhile, the benefit calculation process is based on the maximum difference in total transportation costs without and with the operation of sea tolls. The best network and route results were obtained in the form of optimal benefit and profit performance in the form of networks on the Belawan-Tanjung Priok and Makassar-Tanjung Perak routes, with benefits of Rp. 9,000,000,000,000,- and profits of Rp. 8,600,000,000,-. The other networks each with the highest benefit performance are on the Makassar-Perak route, with benefits of Rp. 8,940,000,000,000,-, profit of Rp. 3,300,000,000, - and the highest profit on the Tanjung Priok-Makassar, Makassar-Tanjung Perak, and Makassar-Sorong route networks, with benefits of Rp. 10,600,000,000,000,- and profit of Rp. 10,800,000,000,-. Meanwhile, if all sea toll route networks are opened, the amount of benefits and profits obtained is Rp. 11,300,000,000,000,- and Rp. - 232,000,000,000,-. This research is expected to contribute in the form ofv improving maritime transportation performance, especially sea tolls and also improving community welfare through the benefits obtained, taking into account the sustainability of sea transportation service providers.